The immunoreceptor adapter protein DAP12 suppresses B lymphocyte–driven adaptive immune responses - Nakano-Yokomizo, Takako (The Rockefeller University Press, 2011)
DAP12, an immunoreceptor tyrosine-based activation motif–bearing adapter protein, is involved in innate immunity mediated by natural killer cells and myeloid cells. We show that DAP12-deficient mouse B cells and B cells from a patient with Nasu-Hakola disease, a recessive genetic disorder resulting from loss of DAP12, showed enhanced proliferation after stimulation with anti-IgM or CpG. Myeloid-associated immunoglobulin-like receptor (MAIR) II (Cd300d) is a DAP12-associated immune receptor. Like DAP12-deficient B cells, MAIR-II–deficient B cells were hyperresponsive. Expression of a chimeric receptor composed of the MAIR-II extracellular domain directly coupled to DAP12 into the DAP12-deficient or MAIR-II–deficient B cells suppressed B cell receptor (BCR)–mediated proliferation. The chimeric MAIR-II–DAP12 receptor recruited the SH2 domain–containing protein tyrosine phosphatase 1 (SHP-1) after BCR stimulation. DAP12-deficient mice showed elevated serum antibodies against self-antigens and enhanced humoral immune responses against T cell–dependent and T cell–independent antigens. Thus, DAP12-coupled MAIR-II negatively regulates B cell–mediated adaptive immune responses.